The voyage of turtle Rex - Cyrus, Kurt. (Boston : Harcourt Children's Books, 2011)
Follows the life of a giant prehistoric sea turtle.
Keywords: Sea turtles -- Juvenile fiction; Stories in rhyme; Sea turtles -- Fiction; Turtles -- Fiction; Marine animals, Fossil -- Fiction; Prehistoric animals -- Fiction